Experience of creating a health-keeping educational environment in higher educational institutions as a condition for developing students’ health-keeping competence. - Brytan, Yu. (Problems of Engineer-Pedagogical Education, 2019)
Proclaiming health-keeping competence the key one for any future specialist in any industry leads to the necessity to seek ways for its development within the vocational training process. The article substantiates the importance and positive role of creating an educational environment in the educational process of learning institutions, which actualizes the need to reveal its influence for students’ health-keeping competence development. Personal pedagogical experience in a higher educational institution (Ukrainian Engineering Pedagogics Academy (Kharkiv)) allowed the author to get convinced of the efficiency of the selected ways of work on creating the educational environment with the aim of developing health-keeping competence of future teachers-engineers. The article offers theory-based and experimentally-verified directions of creating a health-keeping educational environment. Learning about the health-keeping essence of the educational environment as a specially created system where the mastering of knowledge, abilities and skills as well as the development of emotionally-valued attitude toward students’ own health take place within the physical, emotional, intellectual, social and spiritual comfort zone has entailed the substantiation of all its participants (representatives of higher education teaching personnel, tutors of student groups, Faculty senate and dormitory representatives). The coordinated activity of all participants based on their background (goalseeking informative support, explanatory work concerning the methods and focus area) ensures the effective creation of the health-keeping educational environment. The best experience and author’s proposal concerning the methods and forms of work directed at creating a health-keeping educational environment in a higher educational institution can be used by teachers to develop future specialists’ health-keeping competence. It can further be adapted with regard to particular conditions of an institution specializing in training a certain category of future specialists.